السياق السوسيو-تاريخي للفعل المقاولاتي المحدد لطبيعة العمل في المجتمع الجزائري في ظل ثنائيتي - ميهوبي قمر; ميراد حنان (University of Eloued جامعة الوادي, 2024)
نهدف من خلال هذه الدراسة إلى التعرف على تطور العمل عبر الحضارات والمجتمعات، وكذا معرفة التراث السوسيولوجي للفعل المقاولاتي، وذلك بإلقاء الضوء على بعض المقاربات الابستيمولوجية النظرية التي تناولته بالدراسة، للوصول إلى تحديد طبيعة العمل في القطاع المقاولاتي بين ثنائيتي العقلاني واللاعقلاني في المجتمع الجزائري، وهذا انطلاقا من السيرورة السوسيو-تاريخية الذي يتميز بها هذا الأخير، وذلك باستخدام المنهج التحليلي لبعض الدراسات السابقة لعدة باحثين الذين جاءت أبحاثهم في هذا السياق، والتي توصلنا من خلالها أن طبيعة العمل في المجتمع الجزائري قد أخذت مورفولوجيا خاصة تتميز باللاعقلانية في التوظيف، السير وتوزيع الأرباح، وذلك نظرا للسياق السوسيو-ثقافي الذي تطبع فيه أفراد المجتمع الجزائري عن طريق ميكانيزمات التنشئة الاجتماعية وآلياتها المتعددة التي تبلور من خلالها الفعل المقاولاتي بهابيتوس أعطى له طابع خاص، مخالفا لما هو عليه الغرب أين يمتاز بالكثافة، المهارة والاعتماد على الأساليب الموضوعية لاضفاء الصبغة العقلانية على الفعل المقاولاتي والوصول إلى تحقيق الرهانات المسطرة والفعالية المرجوة. Abstract: Through this study, we aim to identify the development of work across civilizations and societies, as well as Knowledge of the sociological heritage of the entrepreneurial act, by shedding light on some of the theoretical epistemological approaches that have been dealt with in the study, in order to determine the nature of work in the entrepreneurial sector between the rational and the irrational in the Algerian society, and this is based on the sociological-historical process that characterizes the latter, And by using the analytical approach of some previous studies of several researchers whose research came in this context, through which we concluded that the nature of work in Algerian society has taken a special morphology characterized by irrationality in employment, traffic and distribution of profits, due to the socio-cultural context in which members of Algerian society are imprinted through The mechanisms of socialization and its multiple mechanisms through which the entrepreneurial act of Habitos crystallized gave it a special character, contrary to what it is in the West, where it is characterized by intensity, skill, and reliance on objective methods to impart rationality. On the entrepreneurial act and access to achieve the bets ruler and the desired effectiveness
العقلاني/اللاعقلاني
Keywords: مقاولاتية; فعل; مقاول; عمل; تمثلات; entrepreneuria; action; representations